Pengaruh Bauran Pemasan dan Nilai Pelanggan terhadap Kepuasan Pelanggan dan Implikasinya kepada Kepercayaan Wisatawan Nusantara pada Objek Wisata - Yudhi Koesworodjati (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2017)
The purpose of this study is to know the phenomenon and get empirical evidence, and alsoconclusion about the influence of service marketing mix and customer value to satisfaction and it’simplications to local tourist trust on tourist destination area in west java province. This research using descriptive and verification methods. The sampling technique is clustered randomsampling. This research surveyed 400 respondents. Data analysis method of this research usingstructural equation model. The result of this research reveals that: (1) Service marketing mix of tourism in Jawa Barat Province is already integrated. (2) Customer value felt by local tourist in Jawa Barat Province is alreadysuperior. (3) Local tourist satisfaction is not satisfied. (4) Local tourist trust in Jawa Barat province is high. (5)The low of local tourist satisfaction is affected by low of service marketing mix performance and customervalue felt by tourist. (6) Satisfaction is determinant factors to local tourist trust.